Organizational culture and leadership behavior affect teacher commitment through job satisfaction - Erlina, Dede; Anisah, Anisah; Hadiyanto, Hadiyanto; Syahril, Syahril (Universitas Jambi, Indonesia, 2026)
Teacher work commitment plays an essential role in improving educational outcomes. However, several indicators suggest that teacher commitment in public junior high schools in Solok City still needs improvement. This study aimed to examine the direct and indirect effects of organizational culture and leadership behavior on teacher work commitment, with job satisfaction as the mediating variable. A quantitative approach with path analysis was employed. The population consisted of 261 civil servant teachers from six public junior high schools in Solok City, with a sample of 159 teachers selected using the Krejcie and Morgan table. Data were collected using a validated Likert-scale questionnaire and analyzed using SPSS. The findings indicate that organizational culture and leadership behavior have significant direct effects on job satisfaction and teacher work commitment. Job satisfaction also significantly influences teacher commitment and mediates the relationship between organizational factors and commitment, suggesting that enhancing job satisfaction can improve teacher commitment and, ultimately, lead to better educational outcomes. These findings highlight the importance of supportive leadership and a positive organizational culture in strengthening teacher commitment and improving school performance.